2003
DOI: 10.1007/s00126-003-0347-2
|View full text |Cite
|
Sign up to set email alerts
|

Cooperite and braggite from the Bushveld Complex: implications for the miscibility gap and identification

Abstract: Analyses of the Pt-Pd±Ni sulphides cooperite, braggite, and vysotskite reported from worldwide occurrences seem to imply a continuum of compositions between vysotskite and cooperite, with no obvious miscibility gap. This is contrary to the experimentally confirmed miscibility gap between cooperite and braggite, and the established compositional gap between co-existing cooperite and braggite from the Merensky Reef. Although the only unambiguous way of distinguishing between cooperite and braggite is to obtain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 45 publications
(69 reference statements)
1
4
0
Order By: Relevance
“…Thus any important changes in composition of platinum-group minerals should occur mainly above the biotite closure temperature and less so under a slower cooling regime. This hypothesis is in agreement with the recent work by Merkle & Verryn (2003), which demonstrated that minerals such as braggite and cooperite equilibrate and change in composition above the blocking temperature of biotite. The clarification of the Bushveld Complex's lower-temperature thermal history would benefit from the application of (U þ Th)/He dating on apatite for example, recently shown (Min et al 2003) to be applicable to rocks more than twice as old as the Bushveld Complex.…”
Section: Discussionsupporting
confidence: 93%
“…Thus any important changes in composition of platinum-group minerals should occur mainly above the biotite closure temperature and less so under a slower cooling regime. This hypothesis is in agreement with the recent work by Merkle & Verryn (2003), which demonstrated that minerals such as braggite and cooperite equilibrate and change in composition above the blocking temperature of biotite. The clarification of the Bushveld Complex's lower-temperature thermal history would benefit from the application of (U þ Th)/He dating on apatite for example, recently shown (Min et al 2003) to be applicable to rocks more than twice as old as the Bushveld Complex.…”
Section: Discussionsupporting
confidence: 93%
“…Cooperite and braggite are dealt with together, as these minerals are hard to distinguish microscopically and they form a chemically nearly continuous series (Cabri 2002, Merkle & Verryn 2003. Notably, cooperite was found in the Makwiro and Umtebekwe Rivers, and braggite in the Makwiro River alone.…”
Section: Cooperite (Pts) and Braggite [(Ptpdni)s]mentioning
confidence: 99%
“…The braggite intergrowth suggests a secondary origin, although the chemistry of a precursor is difficult to constrain. It is known that cooperite is the highest-temperature Pt sulfide in the Bushveld reefs and it may be replaced or overgrown by later braggite at the late magmatic stage (Merkle and Verryn, 2003; Yudovskaya et al ., 2017). The Ni-rich braggite and vysotskite (Pd,Ni)S are not widespread in the Bushveld reefs, rather they are known to be formed under postmagmatic hydrothermal conditions, for example, in massive sulfides ores of the Noril'sk deposit (Genkin et al ., 1981).…”
Section: Resultsmentioning
confidence: 99%